If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7y + 45 = y + -3 Reorder the terms: 45 + 7y = y + -3 Reorder the terms: 45 + 7y = -3 + y Solving 45 + 7y = -3 + y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-1y' to each side of the equation. 45 + 7y + -1y = -3 + y + -1y Combine like terms: 7y + -1y = 6y 45 + 6y = -3 + y + -1y Combine like terms: y + -1y = 0 45 + 6y = -3 + 0 45 + 6y = -3 Add '-45' to each side of the equation. 45 + -45 + 6y = -3 + -45 Combine like terms: 45 + -45 = 0 0 + 6y = -3 + -45 6y = -3 + -45 Combine like terms: -3 + -45 = -48 6y = -48 Divide each side by '6'. y = -8 Simplifying y = -8
| -x+21=x+9 | | a-17=48 | | 3b-3=9 | | (4x+8)-(2x+4)=2x | | 2x+5(5x-1)=-113 | | 10(c-7)=-36 | | 7/9-= | | 5y/9=45 | | (4x+6)-(2x+4)=2x | | 9x(x+9x)= | | -4.5n+3= | | 3y+20=14 | | 12s-24=0 | | 2(y+1)-5=-15 | | 4j-36=0 | | 8-41=40 | | 4k-42=-1 | | 6+4r=2(r-4) | | 4h-42=-18 | | -10.1=w+.3 | | 5x-3=2x+26 | | 7w+3w=40 | | 7r^2+91r+280=0 | | 23=13+2a | | 200+2x=4x+400 | | 9b-36=0 | | -7x-14y=14 | | -2(5-3x)-6(2x-4)=x+1 | | -12+4t=0 | | 3(5x+39)=(X+26) | | -2x+17=x+8 | | 25=25+9r |